Risk Factors and Rates for Hypocalcemia After Pediatric Thyroidectomy: A Systematic Review and Meta‐analysis - Marina Aweeda; Carly Fassler; Daniel R. S. Habib; Alexis B. Miller; Carlos Ortega; Kavita Prasad; Chiu‐Lan Chen; Sara H. Duffus; Ryan H. Belcher (OTO Open)
Abstract Objective Postoperative hypocalcemia after total thyroidectomy (TT) affects pediatric patients at higher rates than adult patients, yet its rate remains poorly defined. This study aims to determine the rates of transient, permanent, and any hypocalcemia after TT in pediatric patients and analyze potential risk factors. Data Sources PubMed, EMBASE, Scopus, and Cochrane. Review Methods A database search was conducted through March 2024 according to the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines. Data concerning postoperative hypocalcemia, risk factors, and clinical context were collected and analyzed. Transient hypocalcemia was defined as lasting less than 6 months and permanent as lasting greater than 6 months after surgery. Results In total, 67 studies with 7331 pediatric patients met the inclusion criteria. Surgical indications for TT in this cohort included malignant conditions (54.75%), benign conditions (19.70%), Graves' disease (18.59%), genetic syndromes (MEN2A/2B, RET mutation) (6.04%), and Hashimoto's thyroiditis (0.92%). The pooled incidence rates were 25.2% (95% CI 0.20‐0.31) for transient, 7.4% (95% CI 0.05‐0.10) for permanent, and 32.1% (95% CI 0.26‐0.39) for any hypocalcemia. Fifteen of the included studies also examined risk factors for postoperative hypocalcemia. Patients undergoing TT for malignancy (odds ratio [OR] 2.82, 95% CI [1.18‐6.73]; P = .02) or Graves' disease (OR 6.12, 95% CI [3.10‐12.01]; P < .0001), as well as those undergoing any lymph node dissection (OR 3.71, 95% CI [1.95‐7.06]; P < .0001) were at higher risk for postoperative hypocalcemia. Conclusion Hypocalcemia is a common postoperative complication of TT in pediatric patients. Risk factors include malignant surgical indication, Graves' disease, and any lymph node dissection.